Mouse Models of Pain in Sickle Cell Disease. Issue 1 (28th September 2018) - Sagi, Varun; Song‐Naba, Waogwende L.; Benson, Barbara A.; Joshi, Sonal S.; Gupta, Kalpna
Abstract: Sickle cell disease (SCD) is a genetic blood disorder that impacts millions of individuals worldwide. SCD is characterized by debilitating pain that can begin during infancy and may continue to increase throughout life. This pain can be both acute and chronic. A characteristic feature specific to acute pain in SCD occurs during vaso‐occlusive crisis (VOC) due to the blockade of capillaries with sickle red blood cells. The acute pain of VOC is intense, unpredictable, and requires hospitalization. Chronic pain occurs in a significant population with SCD. Treatment options for sickle pain are limited and primarily involve the use of opioids. However, long‐term opioid use is associated with numerous side effects. Thus, pain management in SCD remains a major challenge. Humanized transgenic mice expressing exclusively human sickle hemoglobin show features of pain and pathobiology similar to that in patients with SCD. Therefore, these mice offer the potential for investigating the mechanisms of pain in SCD and allow for development of novel targeted analgesic therapies. © 2018 by John Wiley & Sons, Inc.